Pengaruh inflasi kemiskinan dan impor terhadap pertumbuhan ekonomi Indonesia Tahun 1990-2019 - Rizky Adi Maulana; Lucia Rita Indrawati (e-Journal Perdagangan Industri dan Moneter, 2022)
Economic growth is a very interesting phenomenon and needs to be taken seriously and become a benchmark to see how successful the country's economic development is, and used as a tool to design and determine future development policies. Indonesia's economic growth changes every year. This change is due to many things that affect it. This study aims to analyze the effect of inflation, poverty, and imports on economic growth from 1990 to 2019. The method used in this study is the error correction model (ECM). In this study, the results obtained that partially poverty and inflation have a significant negative effect, while imports are significantly positive for economic growth in both the short and long term. Simultaneously, all the variables in the model have a significant effect on economic growth.